Effects of gender on language acquisition in children across different cultures : a systematic review - Chew, Cheryl Jie Shuang (Nanyang Technological University, 2021)
The present systematic review aims to evaluate the quality of evidence of existing literature regarding the gender effects on child language acquisition and any possible cultural influences on this relationship based on the longstanding stereotype that girls perform better in terms of language skills. Out of the 597 unique studies collated, only 30 studies were qualitatively analysed. From these 30 studies, only 15 of them presented with adequate power to detect a moderate effect. 13 of the 15 studies revealed a clear directional effect and scored on a range of 5 to 10 points out of the 12 quality indicators. Our main findings revealed that: (1) there is insufficient research that focuses on the gender effects on child language acquisition, (2) the quality of evidence of existing published literature is substandard, and (3) there is a severe lack of cultural diversity in research. These findings highlight the need for more research to be done in this area, and with more clarity and transparency, given the possible negative impacts of gender stereotypes being imposed on children. Furthermore, researchers should include samples from a wider variety of geographical locations so that evidence will not be skewed towards the WEIRD populations.